In vitro and In Silico Studies on Curcumin and Its Analogues as Dual Inhibitors for cyclooxygenase-1 (COX-1) and cyclooxygenase-2 (COX-2) - Nunung Yuniarti; Perdana Adhi Nugroho; Aditya Asyhar; Sardjiman Sardjiman; Zullies Ikawati; Enade Perdana Istyastono (Journal of Mathematical and Fundamental Sciences, 2012)
Curcumin has been widely reported as an anti-inflammatory agent isolated from the plant Curcuma longa L. (turmeric). This anti-inflammatory activity was associated with the ability of this compound to inhibit the activity of both cyclooxygenase-1 (COX-1) and cyclooxygenase-2 (COX-2) in arachidonic acid metabolism. Dual COX-1 and COX-2 inhibitors are preferred to be employed in the therapy of chronic inflammatory diseases compared to selective inhibitors, since it was reported that the use of selective inhibitors led to severe adverse side effect. In the present study, in vitro and in silico assays on curcumin and its analogues as dual inhibitors for both COX-1 and COX-2 were performed. The results provide theoretical contribution in understanding the ligand-protein interactions at the molecular level to develop new curcumin analogues which possess better anti-inflammatory activity as well as to avoid unsolicited side effects.